Supervisi Akademik Berbantuan Google Workspace for Education untuk Meningkatkan Kompetensi Guru Melaksanakan Pembelajaran Berdiferensiasi - Asih Subekti (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This study aims to describe the increase in teacher competence in carrying out differentiated learning through the application of Google Workspace for Education-assisted academic supervision to Manyaran 1 Public Elementary School teachers. This study uses a qualitative approach with descriptive research methods. Data collection techniques used are observation, interviews, documentation, and triangulation. The data that has been collected were analyzed using qualitative analysis. The results of the study show that academic supervision assisted by Google Workspace for Education is able to increase teacher competency in implementing differentiated learning. In addition, academic supervision assisted by Google Workspace for Education can be a solution in increasing teacher competence in implementing differentiation learning, this is clearly seen in learning which has an impact on improving student services according to their readiness, interests, and learning profile.